Total factor productivity, deforestation, and voluntary sustainability standards: Evidence from Rwandese coffee farmers - Bruno Paz; Bernhard Dalheimer; Meike Wollni (Georg-August University of Göttingen, RTG 2654 Sustainable Food Systems, 2024)
Increasing food demand will most likely be met with agricultural intensification and land clearing, exacerbating environmental consequences associated with food supply. The mechanisms and trade-offs between agriculture and the environment are heterogeneous and not well understood, yet key to enhance food production while safeguarding the environment, ensuring a dual purpose of food systems. This study examines the relationship between voluntary sustainability standards (VSS) and Rwandese coffee farmers' technical efficiency and productivity while exploring the mechanisms behind potential trade-offs and synergies between certification, productivity, and forest protection. Using cross-sectional farm-level data of 842 coffee farmers in Rwanda, we measure the effect of VSS on technical efficiency and an enhanced vegetation index (EVI) reflecting vegetation health and density around the farm. We combine a stochastic frontier analysis controlling for sample selection bias with mediation analysis. Our analysis shows that certified farmers exhibit greater technical efficiency levels than non-certified farmers. We can attribute this to better farm management, leading to 19% and 4% increases in their productivity and technical efficiency, respectively. Our analysis also suggests that certifications lead to higher enhanced vegetation index scores in and around the coffee plots, which we attribute to the regulatory mechanisms associated with certification. We conclude that VSS can enhance coffee production while safeguarding the environment and being a valuable component of a more comprehensive rural development program.
Keywords: D22; D24; Q12; Q15; Q23; Q24; Q15; Q18; Q56; O13; 330; voluntary sustainability standards; coffee; technical efficiency; forest quality; Rwanda